INCREASING THE LEVELS OF ACTIVE COMPOUNDS AND MICROPROPAGATION OF TWO VARIETIES OF CAT WHISKERS (ORTHOSIPHON ARISTATUS (BLUME) MIQ.) THROUGH IN VITRO CULTURE MODIFICATION - Faramayuda, Fahrauk
Cat's whiskers (Orthosiphon aristatus (Blume) Miq.) is a medicinal plant widely used in traditional medicine. The cat's whiskers plant is known to have many properties, including diuretic, helping to lower blood pressure, lowering blood sugar levels, and antiviral. There are three varieties of cat whiskers in Indonesia, i.e., white, white-purple, and purple varieties. The main compounds that play a role in the pharmacological activity of a cat's whiskers are sinensetin, rosmarinic acid, and eupatorin. Due to the low levels of these three compounds, it is necessary to increase the level using a modified in-vitro method through cell suspension culture with the addition of elicitor and precursor. Since the number of white-purple and purple cat whiskers had decreased, so it also requires to make in vitro plant propagation (micropropagation) efforts. The initial stage of this study was conducted by analyzing the phytochemical profiles of those two varieties of cat whiskers, including monitoring of TLC (thin layer chromatography) profiles and determination of the levels of rosmarinic acid, sinensetin and eupatorin using HPLC (high performance liquid chromatography). The increase in secondary metabolite levels by cell cultures was started with callus induction on MS (Murashige and Skoog), Gamborg, SH (Schenk and Hildebrandt), and N6 base media supplemented with various concentration of growth regulator 2,4-D (2,4-Dichlorophenoxyacetic acid) of 0.4; 1, and 2 mg/L. Callus derived from SH media was developed into cell suspension culture. The modified cell suspension culture was carried out by adding elicitor of salicylic acid (14; 70; 140 mg/L), Cu 2+ (30; 40; 50 µM), pectin (0.05; 0.1; 0.2% w/v) and AgNO3 (80; 100; 120 mol/L), precursors of cinnamic acid, coumaric acid, caffeic acid and ferulic acid with a concentration of 0.1; 0.5; and 1 mM. Observations were made on cell suspension cultures with the best growth, including increased levels of secondary metabolites and enzymes phenylalanine ammonia-lyase (PAL) and 4-Coumarate coenzyme A ligase (4CL) activity. Efforts to propagate plants in vitro culture were carried out by introducing shoots on MS media with BAP (Benzyl amino purine) and NAA (Naphthalene acetic acid) added. Root induction was carried out on MS media with 0.5, 0.75, and 1 mg/L IBA (Indole 3-butyric acid) added, then acclimatization was carried out until the plants were ten months old. The levels of secondary metabolites for plants resulting from micropropagation were determined by comparing them with native plants (wild type). The levels of rosmarinic acid and sinensetin were higher in the purple variety, while the highest levels of eupatorin were found in the white-purple variety. Callus derived from SH media added with 2,4-D 0.4 mg/L had a good texture and identified the presence of rosmarinic acid so that it could be developed to the cell suspension culture stage. The addition of 40 M Elicitor Cu 2+ and 1 mM cinnamic acid precursor to cell suspension culture containing 0.4 mg/L SH + 2,4-D media could increase the levels of rosmarinic acid and sinensetin in two varieties of cat whiskers. Media MS + BAP 2 mg/L + NAA 3 mg/L and MS + Zeatin 3 mg/L + 2,4-D 2 mg/L could grow shoots two varieties of cat whiskers. When the acclimatization process was carried out, the planlet could grow well up to 10 months old. The levels of rosmarinic acid and sinensetin in the two varieties of the cat whiskers (in vitro culture) were higher than the wild type. The highest levels of rosmarinic acid and sinensetin in the suspension culture of the whitepurple variety added with 1mM cinnamic acid were 10.22 mg/g dry weight and 17.80 mg/g dry weight. In analyzing levels on day 17 of suspension culture of white-purple variety added with 1 mM cinnamic acid, it was observed that there was an increase in the levels of rosmarinic acid by 104.4% and sinensetin by 256.0%. In the suspension culture of the purple variety modified with the addition of 1mM cinnamic acid, the highest rosmarinic acid level was observed on day 17 (10.67 mg/g dry weight), while the highest concentration of sinensetin occurred on day 19 with a value of 22.5 mg/g dry weight. The levels of rosmarinic acid and sinensetin had increased respectively by 133.01 % (day 17) and 399.0 % (day 17). In the suspension culture of white-purple variety added with 1 mM cinnamic acid precursor, the activity of PAL and 4Cl enzymes had increased on day 5 in which it was indicated by an increase in the maximum activity for PAL and 4CL proteins of 12 kat/g (day 17) and 9.6 kat/g (day 15). Meanwhile, the purple variety had increased from day 13 (PAL) and 11 (4CL) with maximum activity on day 17 for PAL with a value of 4.98 µkat/g protein and 4CL 5.9 µkat/g protein. An increase in activity of PAL and 4Cl enzymes in the suspension culture of two varieties of cat whiskers added 1mM cinnamic acid precursor was in line with the increased in secondary metabolite levels. The shoots of two varieties of cat whiskers derived from MS media + Zeatin 3 mg/L + 2,4-D 2 mg/L could grow well in the acclimatization process until the age of 10 months. The white-purple varieties of cat whiskers from in vitro cultured had higher secondary metabolite levels than the wild type. The highest levels of rosmarinic acid, sinensetin, and eupatorin were found in the ethyl acetate extract of the white purple variety (in vitro plant) with values of 1.08%, 1.62%, and 1.66 %w/w, while in purple variety 1.26, 4.15, 1.54% w/w. In the ethyl acetate extract of the white-purple variety of cat whiskers compared to the wild type, there was an increase in the levels of rosmarinic acid by 248.38 %, sinensetin 362.85%, and eupatorin 76.59%. There was also an increase in the ethyl acetate extract of the purple variety of whiskers cat plant from in vitro culture with the improvement of 41.57% for rosmarinic acid, sinensetin 371.59%, and eupatorin 340%. The results of this study are expected to be used as the basis for the development of secondary metabolite production and cat whiskers plant seeds that have better quality on a larger scale (bioreactor).